Ubiquitin proteasomal system is a potential target of the toxic effects of organophosphorus flame retardant triphenyl phosphate - YILMAZ GÖLER, AYŞE MİNE (My University, 2022)
© 2022 Elsevier B.V.The consumption of the widely used flame retardant Triphenyl phosphate (TPP) is increasing. It is now frequently detected in the environment and also domestically. Although the possibility of dermal exposure to TPP is quite high, little is known about its potential molecular toxicity mechanisms. In this study, we found that TPP caused cytotoxicity on human skin keratinocytes (HaCaT) and significantly inhibited the proliferation and cell migration in a concentration-dependent manner. Additionally, HaCaT cells were sensitive to TPP-induced apoptosis. Reactive oxygen species production was induced with TPP, which increased the protein carbonylation and lipid peroxidation levels. Moreover, TPP inhibited proteasome activity and increased the accumulation of ubiquitinated proteins. Exposure to TPP significantly increased the HSP90, HSP70, GRP94 and GRP78 protein levels. Overall, our findings indicate that TPP may pose a risk to human health and contribute to the current understanding of the risks of TPP at the molecular level.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Farmakoloji ve Toksikoloji; ÇOK DİSİPLİNLİ BİLİMLER; FARMAKOLOJİ VE ECZACILIK; TOKSİKOLOJİ; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; PHARMACOLOGY & TOXICOLOGY; MULTIDISCIPLINARY SCIENCES; PHARMACOLOGY & PHARMACY; TOXICOLOGY; Toksikoloji; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Sağlık, Toksikoloji ve Mutajenez; Multidisipliner; Fizik Bilimleri; Pharmacy; Toxicology; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Health, Toxicology and Mutagenesis; Multidisciplinary; Physical Sciences; Triphenyl phosphate; Proteasome activity; Oxidative stress; Heat shock stress; Endoplasmic reticulum stress; OXIDATIVE STRESS; LIPID-METABOLISM; HAND WIPES; EXPOSURE; INDOOR; DUST; WATER; PLASTICIZERS; INHIBITION; MECHANISMS